Microwave-assisted, [Bmim]HSO4-catalyzed the Friedländer Quinoline Synthesis of Quinoline Under Solvent-free Conditions - Duc, Dau X.; Dung, Vo Cong (Current Organocatalysis, 2022)
An efficient and green method for the Friedländer quinoline synthesis has been described. The synthesis was performed under microwave irradiation using ionic liquid [Bmim]HSO4 as a catalyst. A diverse range of quinoline derivatives was obtained in high yields from 2-aminoaryl aldehydes and ketones under solvent-free conditions.
Keywords: ionic liquid